2017
DOI: 10.7324/japs.2017.70713
|View full text |Cite
|
Sign up to set email alerts
|

Silan/biopolymer microgels for functionalization of cotton fabric: dual responsive pH and temperature and antibacterial properties

Abstract: Biopolymer/chitosan/silan composite wassynthesized in four form by conjugating of chitosan with different biopolymer compounds namely, β-Cyclodextrin (β-CD), Arabic gum, Guar gum and Pullulan in presence of 3-glycidoxypropyltrimethoxysilan (GPTMS) as a cross-linker. Characterisation of the prepared composites has been done through some measurements. FT-IR confirmed the chemical reactions between biopolymers, chitosan andGPTMS.TEM and particle size confirm that, the particles are in small size ranged from 20 -2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Biopolymer/chitosan/silane composite was synthesized in four forms by conjugating of chitosan with different biopolymer compounds namely, β-Cyclodextrin (β-CD), Arabic gum, Guar gum and pullulan in presence of 3-glycidoxypropyltrimethoxysilan (GPTMS) as a cross-linker. Treated fabrics with chitosan-based microgels were characterized and it is confirmed that, the prepared composites impart a hydrophobicity, pH and temperature thermo-sensitive properties to the cotton fabrics [26].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Biopolymer/chitosan/silane composite was synthesized in four forms by conjugating of chitosan with different biopolymer compounds namely, β-Cyclodextrin (β-CD), Arabic gum, Guar gum and pullulan in presence of 3-glycidoxypropyltrimethoxysilan (GPTMS) as a cross-linker. Treated fabrics with chitosan-based microgels were characterized and it is confirmed that, the prepared composites impart a hydrophobicity, pH and temperature thermo-sensitive properties to the cotton fabrics [26].…”
Section: Introductionmentioning
confidence: 75%
“…Cellulose is one of the natural organic polymers. Cellulosic fabrics have been functionalized to add properties such as flame retardancy [1][2][3][4][5][6][7], water/oil repellence [8][9][10][11], antimicrobial [12][13][14][15][16][17], metal adsorption [18][19][20][21][22], gloss properties [23], rodent repellence [24], anti-UV protection [10,25], Stimuli-responsiveness to temperature, and pH [13,26], heat storage, [27][28][29][30] via a variety of methods, including polymeric material deposition and/or infiltration [31][32][33][34][35][36][37], and nano-coating methods [4,20,21,[37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%